Prevalence and risk factors of postpartum dyspareunia at three months post- delivery in Sudanese women - Abd. Alkareem, Inas Mohamed Elhassan; Ounsa, Mohamed Ahmed A Gadir; Mohamed, Elsadig Yousif; Mohamed, Elsadig; Abdalla, Sawsan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum dyspareunia affects many women following childbirth: however, the extent of the problem is difficult to estimate. The objectives of the current study were to determine the prevalence of postpartum dyspareunia and to estimate its risk factors. Methods: This is a cross-sectional study conducted at the National Ribat University Hospital, Sudan. The study was carried out on women attended the refer clinics of obstetrics and gynecology and pediatrics departments in the hospital. The sample size was calculated as 380. The data were collected by a pre-tested questionnaire along with a clinical examination of the vulva and vagina after obtaining the ethical approval. The SPSS was used to analyze the data. Results: The prevalence of postpartum dyspareunia in women attended the National Ribat University hospital was 42.6 %. Regarding age, 8 (61.5%) of women less than 20 years of age experienced dyspareunia, 102 (46.4%) and 52 (35.4%) of women whose age was 20-29 years; and more than 29 years experienced the condition. One hundred forty (51.7%) of women who delivered by normal vaginal delivery developed postpartum dyspareunia. Eight (72.7%), 8 (12.5%) and 6 (17.6%) of women delivered by Operative vaginal, Elective C/S and Emergency C/S developed postpartum dyspareunia respectively. One hundred forty-eight (62.4%), 153 (51.3%) women who had decircumcision and episiotomy in last delivery had postpartum dyspareunia respectively. Forty-six (93.3%), fifty-three (86.9%) and 60 (87%) women who had infected episiotomy, scar tissue at episiotomy and tight interoitus developed the condition respectively. Conclusions: The prevalence of postpartum dyspareunia in women attended the National Ribat University hospital was 42.6 %. Regarding age, 8 (61.5%) of women less than 20 years of age experienced dyspareunia, 102 (46.4%) and 52 (35.4%) of women whose age was 20-29 years; and more than 29 years experienced the condition. One hundred forty (51.7%) of women who delivered by normal vaginal delivery developed postpartum dyspareunia. Eight (72.7%), 8 (12.5%) and 6 (17.6%) of women delivered by Operative vaginal, Elective C/S and Emergency C/S developed postpartum dyspareunia respectively. One hundred forty-eight (62.4%), 153 (51.3%) women who had decircumcision and episiotomy in last delivery had postpartum dyspareunia respectively. Forty-six (93.3%), fifty-three (86.9%) and 60 (87%) women who had infected episiotomy, scar tissue at episiotomy and tight interoitus developed the condition respectively.